Systemic errors in clinical studies / Sistemske napake kliničnih raziskav - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
Despite careful planning and implementation of clinical studies, systematic errors occurring during the course of the research cannot be avoided. In a clinical study, such errors can lead to conclusions that are not realistic. These errors can be increased, minimized or even reversed. Finding the cause and scope of such errors are of exceptional importance in a clinical study. The greater the systematic error or 'bias', the greater the possibility for erroneous statistical results becomes. Systematic errors are, therefore, a constant danger for clinical studies. A study is considered to be unsuitable if at least one systematic error is present.